Influence of Political Changes in the Rituals of Kirant Rai Community - Rai, Prabat Kumar (Researcher: A Research Journal of Culture and Society, 2014)
The cultural practices and traditional values of the Kirant Rai community are influenced by a series of political changes and external aggression. Though, Kirant Rai community has a distinct culture, rituals and philosophy based on Mundhum practiced from time immemorial. The political changes have a negative impact in the present context. One of the indigenous aborigines of Nepal are the Kirant Rai community but their perishing culture and external aggression have created an atmosphere where enrich traditional values and identities are all in the verge of extinction. This writing is dedicated in serving the endanger rituals and practices professed by the Kirant Rai community, especially the Bantawa Rai’s . Otherwise, which might be dislocated and nullified in the year to come. DOI: http://dx.doi.org/10.3126/researcher.v1i2.9887 Researcher 1(2) 2013: 72-80